2022
DOI: 10.3389/fpls.2022.974714
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen rates and plant density interactions enhance radiation interception, yield, and nitrogen use efficiencies of maize

Abstract: The contributions of the different leaf layers to maize yields identified as middle leaf > lower leaf > upper leaf, where the vertical photosynthetically active radiation (PAR) in the canopy gradually decreases. We hypothesized that the allocation of more PAR and nitrogen (N) to the highest contributing leaves will would be beneficial for higher yields and N use efficiencies. The N application rate and plant density effectively regulated the canopy light and N distribution. We evaluated the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The increase in maize yield of top organ removal treatments (T2) may be largely due to ameliorated light distribution, enhanced photosynthetic capacity, and altered source-sink ratio ( Liu et al., 2020 ). Previous studies have shown that the PAR was intercepted by leaves above 2/3 of the height of the maize canopy after the tasseling stage ( Tian et al., 2022 ). The contribution of lower strata leaves to yield formation is much lower than their potential ( Liu et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in maize yield of top organ removal treatments (T2) may be largely due to ameliorated light distribution, enhanced photosynthetic capacity, and altered source-sink ratio ( Liu et al., 2020 ). Previous studies have shown that the PAR was intercepted by leaves above 2/3 of the height of the maize canopy after the tasseling stage ( Tian et al., 2022 ). The contribution of lower strata leaves to yield formation is much lower than their potential ( Liu et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a growing awareness of the need for sustainable production practices in agriculture, particularly in terms of fertilizer use (Feyissa et al, 2022;Tian et al, 2022). While fertilizers have a strong positive correlation with maize yield, the studies have shown that fertilizer application in China far exceeds actual crop requirements (Wang et al, 2022c).…”
Section: Effect Of Reduced Fertilizer Application On Growth Index Of ...mentioning
confidence: 99%
“…Huang et al [ 16 ] developed a light interception model and characterized the effect of plant architecture shaped by growth regulators on canopy PAR interception for a modern maize hybrid. The Beer-Lambert rule was further utilized to characterize the vertical distribution of light in maize canopy [ 17 ]. However, the simplification of the relationship between light distribution and canopy structure to exponential attenuation using LAI and the extinction coefficient limited the ability to accurately simulate the highly heterogeneous PAR distribution within the canopy.…”
Section: Introductionmentioning
confidence: 99%